Cognition in a Changing World: Red-Headed Gouldian Finches Enter Spatially Unfamiliar Habitats More Readily Than Do Black-Headed Birds - Mettke-Hofmann, Claudia; Eccles, Georgina R.; Greggor, Alison L.; Bethell, Emily J. (Frontiers in Ecology and Evolution, 2020)
Human activities are increasingly confronting animals with unfamiliar environmental conditions. For example, habitat change and loss often lead to habitat fragmentation, which can create barriers of unsuitable and unfamiliar habitat affecting animal movements and survival. When confronted with habitat changes, animals’ cognitive abilities play an important, but often neglected part in dealing with such change. Animals must decide whether to approach and investigate novel habitats (spatial neophilia) or whether to avoid them (spatial neophobia) due to potential danger. For species with strict habitat preferences, such as the Gouldian finch (Erythrura gouldiae), which is an open habitat specialist, understanding these novelty responses may be especially important for predicting responses to habitat changes. The Gouldian finch is a polymorphic species, with primarily red or black head colors, which are linked to differing behavioral phenotypes, including novelty reactions. Here we investigate responses to novel habitats (open, dense) in the Gouldian finch, manipulating the color composition of same-sex pairs. Two experiments, each consisting of novel open and novel dense habitat, tested birds in opposite head color combinations in the two experiments. We measured the number of approaches birds made (demonstrating conflict between approach and avoidance), and their entry latency to novel habitats. Gouldian finches showed more approach attempts (stronger approach-avoidance conflict) towards the dense as compared to the open habitat, confirming their open habitat preferences. Black-headed birds also hesitated longer to enter the dense habitat as compared to the open habitat, particularly in experiment 1, appearing less neophilic than red-headed birds, which showed similar entry latencies into both habitat types. This is surprising as black-headed birds were more neophilic in other contexts. Moreover, there was some indication that pairings including at least one black-headed bird had a stronger approach-avoidance conflict than pairings of pure red-headed birds. Results suggest that the black-headed birds use a cognitive strategy typical for residents, whereas red-headed birds use a cognitive strategy known for migrants/nomads, which may cognitively complement each other. However, as 70% of the population in the wild are black-headed, the spatial wariness we document could be widespread, which may negatively affect population persistence as habitats change.